Diabetes Patient Counseling: The Pharmacist’s Role - Kohale, Prajwal S. (Asian Journal of Pharmaceutics (AJP), 2024)
The position of a pharmacist has undergone significant transformation in the previous three decades. The focus of pharmacists is shifting from products to patients at the moment. A pharmacist’s role in patient counseling involves educating patients about their conditions, drugs, and lifestyle changes. It has been demonstrated to enhance therapeutic results. Hyperglycemia is a hallmark of the metabolic illnesses known as diabetes mellitus, which is also defined by abnormalities in protein, lipid, and carbohydrate metabolism. Chronic problems can result in macrovascular, microvascular, and neuropathic illnesses. Self-management of diabetes and patient compliance to the recommended medications and lifestyle changes are extremely important, and pharmacists can play a significant role in counseling. The non-pharmacological and pharmaceutical measures should both be covered in the counseling strategy. It is important to educate people about both acute and chronic consequences. There is strong evidence that patient counseling offered by pharmacists increases treatment adherence and improves life quality outcomes in diabetes.